IMPLEMENTATION OF THE COVID-19 DATA INTEGRATION MECHANISM - Binti Azizatun (Journal of Peace, Development and Communication, 2021)
The government has launched a COVID-19 data integration system to solve the chaotic problem of COVID-19 data in Indonesia. Unite Against COVID-19 (BLC) is a database system around COVID-19 as the reference data in determining policy. Once the importance of BLC, researchers sought to assess the implementation of data governance mechanism in the BLC. Researchers used qualitative analysis, with primary and secondary data collection. Researchers interview three information from the ministry of communication and informatics as a public communication team in the task force to accelerate the handling of COVID-19. The results showed that even data management was based on structural, procedural, and relational mechanisms. Structure mechanism has been formed strongly through the task force team from the national to the regions. Procedural data mechanisms, although changing procedures are now at the point of data integration. The relation mechanism shows that the coordination and communication relationship between member task forces has been done quite well where coordination is always done quickly.